Differences between Presentation Methods in Working Memory Procedures: A Matter of Working Memory Consolidation - Ricker, Timothy J. (2013)
Understanding forgetting from working memory, the memory used in ongoing cognitive processing, is critical to understanding human cognition. In the last decade a number of conflicting findings have been reported regarding the role of time in forgetting from working memory. This has led to a debate concerning whether longer retention intervals necessarily result in more forgetting. An obstacle to directly comparing conflicting reports is a divergence in methodology across studies. Studies which find no forgetting as a function of retention-interval duration tend to use sequential presentation of memory items, while studies which find forgetting as a function of retention-interval duration tend to use simultaneous presentation of memory items. Here, we manipulate the duration of retention and the presentation method of memory items, presenting items either sequentially or simultaneously. We find that these differing presentation methods can lead to different rates of forgetting because they tend to differ in the time available for consolidation into working memory. The experiments detailed here show that equating the time available for working memory consolidation equates the rates of forgetting across presentation methods. We discuss the meaning of this finding in the interpretation of previous forgetting studies and in the construction of working memory models.